Audiobooks, origin and evolution: Brief literature review - Souza Gonçalves, Suellen; Nascimento Silva, Patrícia (Advanced Notes in Information Science, 2023)
The audiobook underwent several transformations until it became a digital file marketed on platforms, as it is known today. In order to identify this progress, this research sought to investigate the emergence of audiobooks and their evolution through a brief literature review. For this, a search was carried out on the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (Portal CAPES) to retrieve works that addressed the theme, using descriptors related to the concept of audiobooks. In view of the results obtained, it was observed that audiobooks have their origin and evolution connected with the advancement of sound technology, which has been improved over the years, offering a significant transformation with the conception of the internet. In addition, the adoption of the audiobook as digital content increases equity and accessibility for users, as it is a format capable of inclusion. Despite the advances, the theme of audiobooks still needs more research and studies, since there are still several unknowns about the definition itself, forms of presentation and organization in the digital environment.